Development of dried and rehydratable grated carrots - Cueto, Rubi Atienza; Francisco, Ma. Leonora dL. (1997)
Dried grated carrots which can be easily reconstituted was developed for the purpose of making available to the commercial baking industry a ready-to-use-just-rehydrate processed ingredient for carrot cakes. The dehydration medium used was the cabinet drier at a drying temperature of 50C for 6 to 8 hours. A preliminary study was conducted to determine the most efficient drying procedure to optimize the use of cabinet dryer. The dry-mix-dry method was chosen as the best procedure to come up with a uniform dehydrated product. The study was conducted with three phases. Phase 1 determined which drying time (6, 7 or 8 hours) at 45-55C will produce a uniform dried product and would manifest a high rehydratability rate and ratio. Phase 2 aimed at standardization of the most acceptable product as dictated by the results from Phase 1. In Phase 3, the rehydrated dried product was utilized in baking a carrot cake which was later subjected to sensory evaluation for analysis of color, flavor, mouthfeel and general acceptability. The same procedure was done for the cake baked using freshly grated carrots. Results from Phase 1 showed that drying for 8 hours resulted to a product with low moisture content and good rehydratability. The standardized product obtained a 5.4% moisture content with a rehydratability rate mean value of 3.8 and rehydratability ratio of 8.6. The results obtained demonstrated high reconstitution capacity as well as a high potential for good shelf-stability. Incorporation in carrot cake showed similar characteristics as compared with the one utilizing fresh carrots.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Carrots